Avascular Necrosis of The Hip Joint Due to Fracture Caput Femur: a Case Report - Safitri Indah Masithah; Nabilah Nabilah; Dananti Kusumawindani; Andi Ratna Kartika Maharani (Jurnal Impresi Indonesia, 2025)
Avascular necrosis can occur for a variety of causes, both traumatic and atraumatic. The blood supply to the head of the femur can be easily disrupted, leading to avascular necrosis in 15% to 50% of cases of caput femoris fractures. A 72-year-old woman with a history of falls 3 months before admission to the hospital. There was pain in the left pelvic joint and difficulty walking since then. The patient was diagnosed with avascular necrosis and treated with heparin. The goal is to relieve pain, prevent further damage, restore blood supply, and improve the function of the affected joint.